Pengaruh BOP Terhadap Efisiensi Produksi Pada PT. Indofood Sukses Makmur Tbk - Afifah Sanu Tarigan; Fatimah Ratu Shafwan; Ade Setiawan; Muhammad Ridwan Irawan; Muhamad Syahwildan (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Factory overhead costs are a crucial component in supporting a company's operational activities. Proper management of these costs is crucial for sustainable production. The purpose of this study is to determine whether factory overhead costs influence production process efficiency at PT. Indofood Sukses Makmur Tbk. This study uses a quantitative method with a statistical analysis approach based on relevant theories and hypotheses. The data used are derived from secondary sources, namely the company's annual reports and financial statements published on its official website. The results of this study will provide empirical evidence for the alleged relationship between factory overhead costs and production efficiency at the company.